2018
DOI: 10.1371/journal.pone.0201756
|View full text |Cite
|
Sign up to set email alerts
|

Identification of genomic regions associated with agronomic and biofortification traits in DH populations of rice

Abstract: Rice provides energy and nutrition to more than half of the world’s population. Breeding rice varieties with the increased levels of bioavailable micronutrients is one of the most sustainable approaches to tackle micronutrient malnutrition. So, high zinc and iron content in the grain are primary targets in rice biofortification breeding. In this study, we conducted QTL mapping using doubled haploid (DH) populations, PSBRc82 x Joryeongbyeo and PSBRc82 x IR69428, phenotyped for agronomic traits and micronutrient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
36
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 55 publications
(46 citation statements)
references
References 39 publications
7
36
1
Order By: Relevance
“…Identification of new donors for agronomic, yield and mineral nutrient traits, dissecting their genetic basis and using them to diversify the breeding population is a continuous process in developing high-yielding and nutritious rice varieties [15][16][17] . Several QTLs and genes have been identified and successfully used in rice improvement.…”
mentioning
confidence: 99%
“…Identification of new donors for agronomic, yield and mineral nutrient traits, dissecting their genetic basis and using them to diversify the breeding population is a continuous process in developing high-yielding and nutritious rice varieties [15][16][17] . Several QTLs and genes have been identified and successfully used in rice improvement.…”
mentioning
confidence: 99%
“…Grain iron and zinc contents are positively correlated (Anandan, Rajiv, Eswaran, & Prakash, ; Descalsota et al, ; Descalsota‐Empleo, Amparado, et al, ; Dixit et al, ; Inabangan‐Asilo et al, ; Stangoulis et al, ; Swamy, Descalsota, et al, ; Xu et al, ). Similarly, in this work, grain iron and zinc contents were positively correlated and presented similar correlations with other traits.…”
Section: Discussionmentioning
confidence: 99%
“…Zhang et al () identified QTL for milled grain iron and zinc contents on chromosomes 1 and 7 in 698 germplasm comprising indica and japonica subsets. Swamy, Descalsota, et al () identified one QTL for iron on chromosome 4 and QTL for zinc on chromosomes 2 and 11 in DH populations from crosses between PSBRc82 and Joryeongbyeo and between PSBRc82 and IR69428. Furthermore, Swamy, Kaladhar, et al () reported that QTL for iron and zinc contents are closely colocated in two BC 2 F 3 mapping populations developed by crossing the indica cultivar 'Swarna' with two different accessions of O. nivara .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations